2019
DOI: 10.2147/idr.s218592
|View full text |Cite
|
Sign up to set email alerts
|

<p>Coagulative biomarkers on admission to the ICU predict acute kidney injury and mortality in patients with septic shock caused by intra-abdominal infection</p>

Abstract: Purpose Sepsis-associated coagulopathy (SAC) contributes to the development of multiple organ failure (MOF) and increasing mortality. The present study was conducted to investigate whether coagulative biomarkers on admission to the intensive care unit (ICU) can predict acute kidney injury (AKI) and mortality in patients with septic shock caused by intra-abdominal infection (IAI). Patients and methods An observational retrospective study was conducted in the surgical ICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 47 publications
(37 reference statements)
2
25
0
5
Order By: Relevance
“…IAI is defined as an infection in the abdominal cavity, presenting with the clinical signs of local and systemic inflammation (pain, tenderness, fever, tachycardia and tachypnea) [ 31 , 32 ]. IAIs can be classified according to the time and severity of the infection [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…IAI is defined as an infection in the abdominal cavity, presenting with the clinical signs of local and systemic inflammation (pain, tenderness, fever, tachycardia and tachypnea) [ 31 , 32 ]. IAIs can be classified according to the time and severity of the infection [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mortality associated with AKI is high (40-60%) and the short-and long-term outcomes in the form of chronic or end-stage renal disease are devastating (5). AKI develops in more than 45% of patients with septic shock (21). The mortality rate of our study patients was 59.5%.…”
Section: Discussionmentioning
confidence: 69%
“…Septic shock is associated with higher mortality compared to sepsis (1). Septic shock continues to account for 62% of general deaths and hospital mortality rates are above 40% (21). Mortality associated with AKI is high (40-60%) and the short-and long-term outcomes in the form of chronic or end-stage renal disease are devastating (5).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that D-dimer is related to renal insu ciency. [41][42][43][44][45][46][47][48][49][50] Yang et al found that the D-dimer level could predict AKI and mortality in ST-elevated myocardial infarction patients. 41 Guerchicoff also reached a similar conclusion.…”
Section: Discussionmentioning
confidence: 99%